LC–MS/MS for the simultaneous determination of polar endogenous ADMA and CML in plasma and urine from diabetics. (May 2015) - Jing, Zhiqiang; Kuang, Liqing; Liu, Naifeng; Yang, Jin
Background: Asymmetric dimethylarginine (ADMA) and ε- N -carboxymethyl-l -lysine (CML) are microvascular risk factors and potential biomarkers of diabetic microvascular complication.Results: Sample preparation was achieved using acetonitrile for protein precipitation step. ADMA, CML and IS CML-d2 were separated with gradient on a Welch Ultimate ® XB- NH2 column. The assays were validated according to current bioanalytical guidelines with respect to specificity, linearity (20–1000 ng/ml for ADMA in human plasma, 50–2000 ng/ml in urine, 10–500 ng/ml for CML in human plasma and urine), accuracy and precision, extraction recovery, matrix effect and stability.Conclusion: The LC–MS/MS method was successfully applied to quantification of ADMA and CML in plasma and urine samples from healthy individuals and patients with diabetic nephropathy.